2005
DOI: 10.1080/02652030500309327
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A: Comparative pharmacokinetics and toxicological implications (experimental and domestic animals and humans)

Abstract: The causal factors for the species-and sex-differences associated with ochratoxin-mediated toxicity remain unclear. Variations in kinetic parameters may play a major role in explaining these differences, however, discrepancies and inaccuracies in the toxicokinetics reported in the literature for various species, make comparison and hence the extrapolation to the human situation impossible. The one-and two-compartment open models currently proposed may be insufficient to enable an accurate representation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…The persistence of OTA in kidney as observed in rainbow trout (Fuchs et al 1986) has been attributed to renal reabsorption and is thought to explain kidney toxicity, a major effect in rodents and pig (Dietrich et al 2005). This might also be true for fish considering the specific distribution pattern in kidney found in a study with 14 C-labelled OTA (Fuchs et al 1986;Fuchs & Hult 1992) and also the elevated OTA concentrations in salmon kidney in the present study.…”
Section: Toxicokinetics Of Otasupporting
confidence: 53%
See 1 more Smart Citation
“…The persistence of OTA in kidney as observed in rainbow trout (Fuchs et al 1986) has been attributed to renal reabsorption and is thought to explain kidney toxicity, a major effect in rodents and pig (Dietrich et al 2005). This might also be true for fish considering the specific distribution pattern in kidney found in a study with 14 C-labelled OTA (Fuchs et al 1986;Fuchs & Hult 1992) and also the elevated OTA concentrations in salmon kidney in the present study.…”
Section: Toxicokinetics Of Otasupporting
confidence: 53%
“…Common to all species including humans, and also confirmed for Atlantic salmon in the present study, is, however, the two-phase elimination profile suggesting the applicability of a two-compartment open model with blood as the central compartment and all other tissues as the peripheral compartment (Galtier et al 1981;Li et al 1997;Studer-Rohr et al 2000;Dietrich et al 2005). A further common feature appears to be the presence of a secondary peak in the OTA plasma concentrations, observed in rats, mice and cows, and now also in salmon muscle, kidney and liver, which was explained by a potential enterohepatic recirculation (Fuchs et al 1986;Fuchs & Hult 1992;Li et al 1997).…”
Section: Toxicokinetics Of Otamentioning
confidence: 81%
“…However, the possibility of a carrier-mediated transport must not be discarded. Dietrich et al (2005) suggested the presence of organic anion transporters with the capacity to transport OTA in the jejunum, but Berger et al (2003) showed that these transporters were not implicated in OTA transport across Caco-2-cells. Another factor that may influence the OTA bioavailability is the finding that OTA is a substrate for the ATPBinding Cassette efflux-proteins MRP2 and BCRP in Caco-2-cells (Schrickx et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As stated by Dietrich et al (2005), these observations demonstrate the importance of plasma/protein binding for the biological half-life of OTA. Thus, differences in OTA affinity binding to proteins between sexes or strains, may lead to differences in OTA elimination.…”
Section: Excretionmentioning
confidence: 60%
“…The half-life is a kinetic parameter which directly depends on the volume of distribution and clearance, parameters that are not generally affected by any loss of the substance (such as in the first pass effect) before entering to the systemic circulation. Dietrich et al (2005) stated that the observed differences in elimination half-lives between oral and i.v application routes most likely stem primarily from analytical limitations rather than from real biological effects. For example, the half-lives obtained by Galtier et al (1979) were shorter than the ones reported in the rest of the studies, probably due to the different technique that was used to quantify OTA in the biological matrices or to the lack of timepoints (samples were only collected during the first 48h).…”
Section: Distributionmentioning
confidence: 99%